Pilisszentiván-Hárs-erdő 2024 - Bence Simon; Szilvia Joháczi; Vilmos Lenár; Ákos Müller; László Rupnik; Lőrinc Timár (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
As part of a new research project and a local history research project, a team of the Institute of Archaeological Sciences of the Eötvös Loránd University and Archeovertex Ltd excavated a Roman village in the territory of Pilisszentiván. The settlement is located in the northwestern hinterland of the Roman town of Aquincum (today: Óbuda, Hungary) in a scarcely investigated area. The excavation brought to light two Early Roman buildings with stone foundations, a rich pottery record, several metal finds, and a building associated with workshop activities. New data on the topography of the village was also collected. The results suggest that the population of the settlement had already lived a Roman lifestyle around the turn of the 1st and 2nd centuries AD. In light of this year’s excavation, some of the results of last year’s campaign may be reconsidered.